The Oxford handbook of industrial policy - Oqubay, Arkebe; Cramer, Christopher; Chang, Ha-Joon, 1963-; Kozul-Wright, Richard (Oxford University Press, 2020)
This comprehensive handbook explores the theory and practice of industrial policy across advanced, emerging, and developing economies. It examines the role of the state in promoting competitiveness, structural transformation, and technological capabilities. Contributors address key issues such as globalization, climate change, gender, and governance, offering insights into how industrial policy intersects with macroeconomics, infrastructure, and human capital development.